Fact-checking on Twitter: An analysis of the hashtag #StopBulos - Lobato, Roberto M.; Velandia Morales, Andrea; Sánchez Rodríguez, Ángel; Montoya Lozano, Mar; García Sánchez, Efraín (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
The fact-checking is an important tool to improve the quality of the information that circulates in virtual networks. Although there are different fact-checking verification agencies, we also found some more informal strategies such as the use of the hashtag #Stopbulos. Thus, this research aims to characterize the #StopBulos hashtag on Twitter as a way to verify information and control the spread of fake news. The results showed that there was diversity among users and the themes of the tweets that included this hashtag, while the main function was to deny fake news. However, it was found that those who achieved greater dissemination were the users with the largest number of followers and institutional character. The implications of using the #StopBulos hashtag as a tool to identify false information on social networks are discussed. Keywords: fake news, post-truth, post-news, social media, network societies